Nursing research priorities in critical care in Brazil: Delphi Study - Adriano da Silva Acosta; Sayonara de Fátima Faria Barbosa; Grace Teresinha Marcon Dal Sasso (Universidade de São Paulo, 2020)
Objective: to analyze the nursing research priorities in critical care in Brazil identified by specialists and researchers in the area, as well as to establish the consensus of the topics suggested by the experts. Method: a descriptive study, using the e-Delphi technique in three rounds. The research participants were 116 Brazilian nurses who are experts in critical care in the first round, ending up with 68 participants in the third round of the study. Descriptive statistics were used to analyze the demographic variables and the results of the research topics in the second round. In the final analysis, the Kappa agreement coefficient was calculated, comparing the answers between rounds two and three. Results: 63 research topics were generated, grouped into 14 domains of intensive care practice in the first round, and consensus was settled in the subsequent rounds. Topics such as humanization of care (0.56), bloodstream infection control (0.54), and nursing care for polytrauma patients (0.51) were items rated above 0.50 in the agreement analysis between the topics in the two rounds using the Kappa coefficient. Conclusion: this study provides an important guideline for nursing research in critical care in Brazil, guiding for future research efforts in the area.